(untitled) (Педагогіка вищої та середньої школи, 2009)
The article is the part of complex research on development of organizational mechanisme of adjusting of society of 21th item. In the article pedagogical experience of author is analysed in the contenc of forming of project culture of personality. In the article the examples of tasks are presented as elements of educational and educate process of the indicated orientation in institutes (on specialities there is a "design", "advertising" and the method of their conducting a teacher is described.